Revisiting hysteresis of flow variables in monitoring unsteady streamflows. Issue 6 (9th November 2020) - Muste, Marian; Lee, Kyutae; Kim, Dongsu; Bacotiu, Ciprian; Oliveros, Marcela Rojas; Cheng, Zhengyang; Quintero, Felipe
Abstract : Conventional streamflow monitoring methods entail one-to-one relationships between two flow variables obtained by combining direct flow measurements with statistical analyses. These relationships (i.e. ratings) are used to monitor both steady and unsteady flows despite that in the latter cases the flow variables display an inherent hysteretic behaviour. Such behaviour is prominent if the wave passing through the gauging station is non-kinematic. This paper demonstrates that the index-velocity and continuous slope-area methods are more suitable to monitor unsteady flows in comparison with the widely used stage–discharge approach. Case studies are presented to show that, contrary to current perceptions in practical applications, hysteresis can be captured even in small streams and frequently-occurring run-off events. The paper also highlights the separation of the flow variable hydrographs in unsteady flows. This hysteresis-related aspect is less investigated so far despite having important practical implications for both hydrometric and fluvial transport applications.